2007
DOI: 10.1007/s10265-007-0125-9
|View full text |Cite
|
Sign up to set email alerts
|

Is competition between mesocarp cells of peach fruits affected by the percentage of wild species genome?

Abstract: The number of cells and the mean cell volume in the mesocarps of fruits from peach genotypes with different percentages of the genome of Prunus davidiana, a wild, related, species, were evaluated. The mesocarp mass varied greatly between the four groups of genotypes. The mean cell volume and the number of cells were negatively correlated within each group. This correlation can be interpreted as a relationship of competition between cells. In order to describe the type of competition in the different groups, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…In our study, cell number, not cell size, made contributions to large fruit. This result is consistent with that of Quilot and Génard (2008), who compared four peach groups with different percentages of a wild, smallfruited peach genome. They found that the percentage of the wild peach genome affected maximal mesocarp cell number but not the maximal mesocarp cell size suggesting that increased mesocarp cell numbers resulted in the large fruit size in cultivated peach genotypes.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, cell number, not cell size, made contributions to large fruit. This result is consistent with that of Quilot and Génard (2008), who compared four peach groups with different percentages of a wild, smallfruited peach genome. They found that the percentage of the wild peach genome affected maximal mesocarp cell number but not the maximal mesocarp cell size suggesting that increased mesocarp cell numbers resulted in the large fruit size in cultivated peach genotypes.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, cultivar fruit size variability is generally due to mesocarp cell number rather than cell size in olives (Hammami et al 2011) and other drupes (Scorza et al 1991;Yamaguchi et al 2004;Olmstead et al 2007;Quilot and Génard 2008), and this pattern was observed in layers 5-9. This contrasting behavior indicates a morphogenetic difference between layers 1-4, which behave in a similar manner to the epidermis, and layers 5-9, which behave in the same manner as the mesocarp.…”
Section: Relationships Of Fruit Size To Epidermal and Subepidermal Cementioning
confidence: 89%
“…lular processes that produce the final size of fleshy fruits (Gillaspy et al 1993). Comparative studies attribute cultivar fruit size variation to cell number (Scorza et al 1991;Yamaguchi et al 2004;Olmstead et al 2007;Quilot and Génard 2008;Hammami et al 2011) or both cell number and size when wild genotypes are included in the comparison (Yamaguchi et al 2002;Harada et al 2005). However, although exocarp cell activity is considered to be a relevant component of fruit development (Gillaspy et al 1993;Lemaire-Chamley et al 2005;Fu et al 2010), it has generally not been considered in studies of fruit growth or with respect to genetically based size differences.…”
Section: Introductionmentioning
confidence: 99%
“…In their review of intra-plant competition, Sadras & Denison (2009) concluded that plant individuals might use competition-like mechanisms to allocate resources such as nutrients, but only if it increases overall individual fitness. Competition within plant individuals is known to lead to trade-offs between size and number of plant units (Sadras, 1995;Chikov, 2008;Sadras & Denison, 2009) as well as between vegetative and reproductive structures (e.g., Liu et al, 2007;Quilot & Genard, 2008). The vertical growth of shrubs can also be limited by the abrasive effect of windblown ice particles (Sonesson & Callaghan, 1991), resulting in differential growth patterns among stems.…”
Section: Discussionmentioning
confidence: 99%